Biofilm Formation by ica-Negative Ocular Isolates of Staphylococcus haemolyticus - Sasmita Panda; Durg Vijai Singh (Frontiers in Microbiology, 2018)
Staphylococcus haemolyticus is the second most frequently isolated CoNS from ocular infections and human blood cultures. In this study, we examined 18 ocular S. haemolyticus isolates for their capacity to form biofilm and conducted detachment assay to determine the composition of the biofilm matrix and involvement of various elements in cell lysis. PCR identified the presence of biofilm-associated genes, and ica operon and CLSM visualized the components of the biofilm matrix. We found that PIA-independent biofilm formation is the characteristic feature of S. haemolyticus isolates, irrespective of the sources of isolation, and protein or DNA or both are the major components of the biofilm matrix. Cell lysis enabling DNA release was an essential step for biofilm attachment during the initial stages of biofilm development. The srtA transcript expression study indicates its role in the early stages of biofilm development. We found the presence of antibiotic resistance genes in the eDNA and gDNA thus suggesting the possible role of biofilm in horizontal gene transfer of antibiotic resistance determinants. The overall study indicates that S. haemolyticus formed the biofilm comprising of protein or DNA or both and srtA play a role in the initial development of biofilm.